Cross-section measurements for short-lived isotopes of 46Ti, 75As and 92Mo at the neutron energies from 13.6 to 14.9 MeV - Gültekin, E; Bostan, M; Erduran, MN; Subasi, M; Sirin, M (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
Cross-sections were measured at neutron energies from 13.6 to 14.9 MeV for the reactions Ti-46(n,p) Sc-46m, As-75(n,p) Ge-75m and Mo-92(n,2n) Mo-91m leading to short-lived products. Corrections were made for the effects of gamma ray attenuation, coincidence summing, pulse pile-up, dead time, neutron flux fluctuations and scattered low energy neutrons. Statistical model calculations taking into account precompound effects were also performed. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: Nuclear Science & Technology